Comportamento ecofisiológico de Croton urucurana Baill, Cecropia pachystachya Trécul, Gallesia integrifolia (Spreng.) Harms, Hevea brasiliensis Willd. Ex A. Juss e Psidium cattleianum Sabine - Leal, Mariana Santos (2020)
The ecophysiological behavior of plants is intrinsic to each plant species and is also influenced by environmental conditions such as solar radiation and water availability. Once the ecophysiology of tree species and their interactions with environmental conditions and their water use efficiency are better understood, local water dynamics can be better understood and more efficient management systems adopted. The objective of this study was to characterize, quantify and compare the ecophysiological behavior (transpiration, photosynthesis and stomatal conductance) and the efficiency of water use as a function of environmental variables and soil water availability of five native forest species: Croton urucurana, Cecropia pachystachya, Hevea brasiliensis, Gallesia integrifolia and Psidium cattleianum. The monitoring of the ecophysiological variables was performed in the hour scale, in healthy and expanded leaves of seedlings packaged with the aid of the diffusion porometer, and the leaf water potential was obtained by means of the Scholander pump. The results indicated that the studied species responded differently to environmental conditions (water availability, photosynthetically active radiation and vapor pressure deficit), and in general, the seedlings of all species under conditions of lower leaf water potential had lower rates of gas exchanges, however on a different scale of values. Thus, the restriction of water in the soil caused the plants to decrease their rates in order to avoid excessive water loss.